The effect of macroeconomic uncertainty on household spending - Olivier Coibion; Dimitris Georgarakos; Yuriy Gorodnichenko; Geoff Kenny; Michael Weber (European Central Bank (ECB), 2021)
Using a new survey of European households, we study how exogenous variation in the macroeconomic uncertainty perceived by households affects their spending decisions. We use randomized information treatments that provide different types of information about the first and/or second moments of future economic growth to generate exogenous changes in the perceived macroeconomic uncertainty of some households. The effects on their spending decisions relative to an untreated control group are measured in follow-up surveys. Higher macroeconomic uncertainty induces households to reduce their spending on non-durable goods and services in subsequent months as well as to engage in fewer purchases of larger items such as package holidays or luxury goods. Moreover, uncertainty reduces household propensity to invest in mutual funds. These results support the notion that macroeconomic uncertainty can impact household decisions and have large negative effects on economic outcomes.
Keywords: E3; E4; E5; 330; Uncertainty; household spending; household finance; surveys; randomized control trial